DEVELOPMENT OF AN EVIDENCE-BASED BODYWEIGHT MANAGEMENT AND OBESITY PREVENTION STRATEGY FOR A RURAL COMMUNITY; A STUDY PROTOCOL - Dr. Aurang Zeb (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Obesity presents a significant health challenge globally, influenced by genetic, environmental, and behavioral factors. Its prevalence in Pakistan, particularly in rural communities, contributes to extensive health and economic burdens. This study aims to develop an evidence-based community strategy for bodyweight management and obesity prevention, contextualized within local practices. Using an Explanatory Sequential Mixed-Methods approach, the research involves a systematic review and meta-analysis of obesity interventions, followed by qualitative exploration of community perceptions and experiences. Through purposive sampling, overweight, obese, and normal-weight individuals will participate in interviews, addressing perceptions of ideal weight and strategies for weight management. Trustworthiness will be ensured through rigorous data collection and analysis, adhering to established criteria. Meta-inference, achieved through integrating qualitative and quantitative findings, will guide program development. The proposed program development may enhance the management of obesity in rural Pakistani communities by incorporating evidence-based strategies and community engagement, potentially leading to improved health outcomes.